Changing the culture on labour ward to increase midwives promotion of birthing pools: an action research study - Russell, Kim (2016)
Waterbirth practice has the potential to support a midwifery model of care and yet little is known about how the organisation of care can be changed to improve the use of birthing pools. This action research study focused on a group of midwives working on a labour ward in an English obstetric led maternity unit with 3,800 births and 25 recorded waterbirths per year. Interviews and focus groups with labour ward midwives and managers were employed to identify barriers to birthing pool use and inform the change process. Three problem-solving workshops with labour ward coordinators were organised with the aim of influencing other midwives’ use of birthing pools. Data from a newly developed waterbirth questionnaire and maternity records were used to evaluate change in levels of personal knowledge, waterbirth self-efficacy and social support. Foucauldian discourse analysis and One-Way ANOVA with Tukey post hoc tests were used to analyse qualitative and quantitative data. Fourteen midwives took part in focus groups and seventeen in interviews over four research phases. Interventions, developed by workshop attendees, included improvements to the recording and dissemination of waterbirth and water immersion data, target setting and the appointment of a waterbirth champion. By the end of the study the numbers of waterbirth practitioners, recorded waterbirths and social support increased significantly. Discourse analysis revealed the presence of dominant biomedical and subjugated ‘being with woman’ midwifery discourses.